The Impact of Virality on the Creative Process and Mental Well-Being of Film Creators in the Digital Age - Viony Wijaya; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
The social media viral effect requires movie producers to consider achieving excellence in narrative art as well as incorporating measures for increasing the popularity and profitability of their work. In this script, Behind the Feed, the phenomenon of viral effect is demonstrated through a character named Lintang, a film graduate who utilizes viral effect through buying counterfeit views and followers to save a shelter for street kids, help take care of her family, and entice film companies. This qualitative narrative investigation applies theories related to Deception Behavior Theory and Image Repair Theory in incorporating aspects of how manipulating viral effect leads to a degradation of professional trust and relations. Restoration comes through admitting a mistake, taking corrective actions, and restoring a definition of success based on qualitative aspects opposed to quantity.